Analysis of the Physical and Chemical Properties of Petung Bamboo (Dendrocalamus asper) Charcoal Briquettes - Jannah, Nurul; Rini, Dwi Sukma; Lestari, Dini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Bamboo is a very abundant resource with high diversity. There are 157 types of bamboo in Indonesia, one of which is petung bamboo. Petung bamboo is used as raw material for handicrafts and construction, but much of it remains unused and becomes waste, making it a potential alternative fuel source such as bio-briquettes. This study aims to determine the effect of compression pressure on the characteristics of petung bamboo charcoal briquettes and to determine the suitability of the quality of petung bamboo charcoal briquettes according to SNI 01-6235-2000. The research design used was a non-factorial completely randomized design (CRD) with compression pressure factors consisting of 200 psi, 350 psi, and 500 psi. The conversion of bamboo biomass into charcoal was carried out using the pyrolysis method with a drum kiln. The results showed that the highest average density value was found in treatment T3, which was 0.53 g/cm3, while the lowest average density value of charcoal briquettes was found in treatment T1, which was 0.44 g/cm3. Based on SNI, the moisture content that met the SNI standard was found in treatment T2 (350 psi) < 8%. The ash content of all treatments of charcoal briquettes meets the standard of < 8%, the volatile matter content of all treatments of charcoal briquettes does not meet the standard of <15%, and the calorific value of all treatments of charcoal briquettes meets the standard of > 5000 cal/g. Compression pressure does not affect the characteristics of petung bamboo charcoal briquettes. All characteristics of petung bamboo charcoal briquettes in this study met the SNI No. 01-623-2000 standard, except for the volatile matter content and moisture content at pressures T1 (200 psi) and T2 (350 psi).